Ferroptosis targeting natural compounds as a promising approach for developing potent liver cancer agents - Pandey, Pratibha; Elsori, Deena; Kumar, Rahul; Lakhanpal, Sorabh; Rautela, Indra; Alqahtani, Tariq Mohammed; Ahmad, Fuzail; Iqbal, Danish; Khan, Fahad (Frontiers in Pharmacology, 2024)
Liver cancer is the second leading cause of cancer-related death worldwide. However, treatment options, including surgical resection, transplantation, and molecular drug therapies, are of limited effectiveness. Recent studies have demonstrated that suppressing ferroptosis might be a pivotal signal for liver cancer initiation, thus providing a new way to combat liver cancer. Ferroptosis is a distinct form of controlled cell death that differs from conventional cell death routes like apoptosis, necrosis, and pyroptosis. It results from intracellular iron overload, which raises iron-dependent reactive oxygen species. This, in turn, leads to the accumulation of lipid peroxides that further result in oxidative damage to cell membranes, disrupt normal functioning, and ultimately speed up the ferroptosis phenomenon. Ferroptosis regulation is intricately linked to cellular physiological processes, encompassing iron metabolism, lipid metabolism, and the equilibrium between oxygenfree radical reactions and lipid peroxidation. This review intends to summarize the natural compounds targeting ferroptosis in liver cancer to offer new therapeutic ideas for liver cancer. Furthermore, it serves as the foundation for identifying and applying chemical medicines and natural chemicals that target ferroptosis to treat liver cancer efficiently.